Altered ATP13A2/PARK9 Levels Influence α-Synuclein Accumulation in Neurons via Phagocytosis and Secretion in Glial Cells - Taiji Tsunemi; Yuta Ishiguro; Asako Yoroisaka; Dou Feng; Nobutaka Hattori (Cells)
(1) Background: Parkinson’s disease (PD) is characterized by the pathological accumulation of α-synuclein (α-syn) containing Lewy bodies (LBs) and Lewy neurites (LNs) within neurons. Growing evidence indicates that α-syn may propagate throughout the nervous system in a manner similar to prion-like transmission. Extracellular vesicles (EVs) may contribute to this pathway. We and others have reported that ATP13A2/PARK9 deficiency results in decreased EVs while its overexpression leads to increased EV generation. For analyzing EV-mediated α-syn secretion in neighboring neurons, we planned to alter Atp13a2 levels in vivo. (2) Methods: Three months after inoculating mouse α-syn fibrils into the striatum of Atp13a2-null and wild-type mice, we stained brain sections with anti-phosphorylated α-syn antibodies and then quantified LBs/LNs. We also examined the effect of increased levels of ATP13A2 by injecting lentivirus carrying human ATP13A2. Finally, we used cultured astrocytes and microglia for α-syn uptake and release, which were mediated by EVs. (3) Results: While LBs/LNs were formed in the entire brains, no significant difference was observed in LB/LN formation between Atp13a2-deficient and wild-type mice. Interestingly, the overexpression of ATP13A2 led to decreased LB/LN formation in the entire brains. Microglia and astrocytes released EVs more than neurons. EVs released from microglia and astrocytes contained more α-syn PFFs than those from neurons. (4) Conclusions: These results suggest that enhanced EV secretion by increased ATP13A2 levels attenuate the spreading of α-syn in brains, suggesting a protective role of ATP13A2 in α-synucleinopathies